The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41598-023-41503-9
|View full text |Cite
|
Sign up to set email alerts
|

Osteological, multi-isotope and proteomic analysis of poorly-preserved human remains from a Dutch East India Company burial ground in South Africa

Judyta Olszewski,
Rachael A. Hall,
Lisette M. Kootker
et al.

Abstract: Skeletal remains discovered in Simon’s Town, South Africa, were hypothesised as being associated with a former Dutch East India Company (VOC) hospital. We report a novel combined osteological and biochemical approach to these poorly-preserved remains. A combined strontium (87Sr/86Sr), oxygen (δ18OVPDB) and carbon (δ13CVPDB) isotope analysis informed possible childhood origins and diet, while sex-specific amelogenin enamel peptides revealed biological sex. Osteological analyses presented evidence of residual ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…Similarly, Mays et al [335] identified the sex of highly degraded skeletal remains dated 1 st century BCE overcoming the limitation posed by high-throughput DNA sequencing, that failed as no aDNA survived in such remains. Olszewski et al [336] recently conducted proteomic analyses on human remains from a Dutch East India Company burial ground in South Africa and managed confirm the biological sex of the remains from these poorly preserved samples.…”
Section: Proteomics For Personal Identificationmentioning
confidence: 99%
“…Similarly, Mays et al [335] identified the sex of highly degraded skeletal remains dated 1 st century BCE overcoming the limitation posed by high-throughput DNA sequencing, that failed as no aDNA survived in such remains. Olszewski et al [336] recently conducted proteomic analyses on human remains from a Dutch East India Company burial ground in South Africa and managed confirm the biological sex of the remains from these poorly preserved samples.…”
Section: Proteomics For Personal Identificationmentioning
confidence: 99%